2020
DOI: 10.1111/ijsa.12305
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of change in applicants' perceptions of fairness

Abstract: Using an event‐triggered multi‐stage framework, this random‐effects meta‐analysis examined the changes in applicants' perceptions of fairness between consecutive stages and throughout the entire personnel selection process. We integrated findings of studies with at least two measurement points, resulting in 45 effect sizes (overall N = 3,038). Trajectories of perceptions of fairness decreased nonlinearly across the process, with a steeper decrease for people who held high levels of initial fairness expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Research shows that procedural justice perceptions of applicants might change throughout the selection process, as applicants have varying expectations in each stage (Konradt et al, 2020). Hence, an examination of the fairness perceptions of selection methods with a high degree of digitalization compared to those with a low degree of digitalization in consideration of the respective stage of the application process appears to be meaningful.…”
Section: Hypothesis 1: the Use Of Selection Methods With High Degrees Of Digitalization Has A Positive Effect On Applicants' Perceptions mentioning
confidence: 99%
“…Research shows that procedural justice perceptions of applicants might change throughout the selection process, as applicants have varying expectations in each stage (Konradt et al, 2020). Hence, an examination of the fairness perceptions of selection methods with a high degree of digitalization compared to those with a low degree of digitalization in consideration of the respective stage of the application process appears to be meaningful.…”
Section: Hypothesis 1: the Use Of Selection Methods With High Degrees Of Digitalization Has A Positive Effect On Applicants' Perceptions mentioning
confidence: 99%
“…In terms of digital selection methods, applicants tend to show favourable reactions to online test-based procedures (McCarthy et al, 2017), although the reaction to online interviews via videoconferences showed less positive applicant reactions (McCarthy et al, 2017;Woods et al, 2019). A recent and unique metaanalysis in that they looked at studies of applicant reactions with at least two measurement points found that the perceptions of fairness declined nonlinearly across the selection process (Konradt et al, 2020). Those with higher levels of initial fairness expectations experienced a steeper decline in fairness perceptions, which was less strong when the interval between post-test and post-decision was longer.…”
Section: Applicant Reactions and Impression Managementmentioning
confidence: 99%